Media for advocacy of mental health in the Ethiopian context. Current practice, gaps, and future directions - Anbessie, Mohammed N.; Belete, Yonas L.; Ayele, Biniyam A.; Valcour, Victor; Kavanagh, Niall; Prioleau, Caroline; Yohannis, Kalkidan (Frontiers in Psychiatry, 2023)
Media plays a crucial role in reshaping societal attitudes and behaviors towards individuals with mental illness. It contributes to improved rights of people living with mental health conditions and access to care services. However, in Ethiopia, mental health advocacy faces obstacles such as deep-rooted misconceptions, fear, and discrimination about mental illness, as well limited engagement of stakeholders and language barriers. Both mainstream and social media play a large role in disseminating mental health topics in Ethiopia. However, they need organized initiatives and efforts in order to be successful in promoting mental health awareness to the public. Implementing a comprehensive strategy comprising public awareness campaigns, policy advocacy, community engagement, stakeholder collaboration, responsible reporting, and increased coverage of mental health topics is crucial. The World Health Organization also emphasizes the role of health ministries in supporting mental health advocacy efforts. By promoting education, challenging stigmas, and improving access to mental health services, media advocacy can contribute to creating a more informed and supportive society for individuals with mental illness in Ethiopia.